The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.cmet.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Rab10, a Target of the AS160 Rab GAP, Is Required for Insulin-Stimulated Translocation of GLUT4 to the Adipocyte Plasma Membrane

Abstract: GLUT4 trafficking to the plasma membrane of muscle and fat cells is regulated by insulin. An important component of insulin-regulated GLUT4 distribution is the Akt substrate AS160 rab GTPase-activating protein. Here we show that Rab10 functions as a downstream target of AS160 in the insulin-signaling pathway that regulates GLUT4 translocation in adipocytes. Overexpression of a mutant of Rab10 defective for GTP hydrolysis increased GLUT4 on the surface of basal adipocytes. Rab10 knockdown resulted in an attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
337
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(367 citation statements)
references
References 56 publications
22
337
2
Order By: Relevance
“…These data all support the hypothesis that AS160 negatively regulates the activity of Rab protein(s) involved in GLUT4 translocation. Recently, it has been suggested that Rab10 is the Rab protein downstream of AS160, since introduction of the constitutively active Rab10 (Rab10 Q67L ) increases the PM fraction of GLUT4 in the absence of insulin stimulation, and knockdown of Rab10 retards insulin-stimulated GLUT4 translocation [8,9]. These findings further support the existence of a negative regulatory mechanism between AS160 and Rab protein(s).…”
Section: Introductionsupporting
confidence: 70%
“…These data all support the hypothesis that AS160 negatively regulates the activity of Rab protein(s) involved in GLUT4 translocation. Recently, it has been suggested that Rab10 is the Rab protein downstream of AS160, since introduction of the constitutively active Rab10 (Rab10 Q67L ) increases the PM fraction of GLUT4 in the absence of insulin stimulation, and knockdown of Rab10 retards insulin-stimulated GLUT4 translocation [8,9]. These findings further support the existence of a negative regulatory mechanism between AS160 and Rab protein(s).…”
Section: Introductionsupporting
confidence: 70%
“…Four Rabs, Rab2, Rab8a, Rab10, and Rab14, have been shown as substrates of AS160 in an in vitro assay (6), among which Rab10 and Rab8a regulate GLUT4 exocytosis in 3T3-L1 adipocytes (43) and L6 myocytes (44), respectively. Interestingly, a recent report (45) shows that Rab14 may regulate the endocytic trafficking of GLUT4 in 3T3-L1 adipocytes.…”
mentioning
confidence: 99%
“…AS160 has a Rab GTPase-activating protein (GAP) domain that plays a critical role in regulating vesicle formation, vesicle movement, and membrane fusion [11] . Phosphorylation of AS160 is suspected to exhibit impairments in its Rab GAP activity, which permits target Rabs to return to their active GTP-bound forms and initiate GLUT4 exocytotic trafficking [12,13] . AS160 phosphorylation is reduced in T2DM patients, which is accompanied by impaired GLUT4 translocation [14] .…”
Section: Introductionmentioning
confidence: 99%